2021
DOI: 10.1093/socpro/spab056
|View full text |Cite
|
Sign up to set email alerts
|

“Addiction Doesn’t Discriminate”: Colorblind Racism in American Rehab

Abstract: Drawing on ethnography and interviews with recovering men in the Twin Cities, Minnesota, this study explores how two dominant models of American rehab are racialized — coerced treatment theorizing addiction as criminal personality—and a more medicalized, voluntaristic model rooted in the brain disease paradigm. At the “carceral rehab” of “Arcadia House,” staff assumed its majority court-mandated, poor men of color would arrive resistant to reforming their “lifestyle addictions,” justifying treatment backed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…As such, white men embody the purest case of the contemporary "hijacked brain" trope. (Our own case presents a striking and almost exclusive differentiation between the neurochemical medicalization of white men (Whetstone, 2021) and the psychological medicalization of white women (Hill and Crawford, 1990). )…”
Section: The Whiteness Of Brain Diseasementioning
confidence: 64%
See 1 more Smart Citation
“…As such, white men embody the purest case of the contemporary "hijacked brain" trope. (Our own case presents a striking and almost exclusive differentiation between the neurochemical medicalization of white men (Whetstone, 2021) and the psychological medicalization of white women (Hill and Crawford, 1990). )…”
Section: The Whiteness Of Brain Diseasementioning
confidence: 64%
“…Yet white men remain more redeemable, positioned on the edge of the "criminal addict" construct, where they can either benefit from or lose white privilege (see, for example, Kerrison, 2015;Tiger, 2013). In integrated programs, they tend to be treated as prize pupils, "older brothers" who can teach their more culturally deficient brothers of color (Whetstone, 2021).…”
Section: The Whiteness Of Brain Diseasementioning
confidence: 99%
“…Contributing to literature on the medicalisation of eating‐ and food‐related conditions, the case of lactose intolerance and lactase persistence highlights how biocentric biases are reified through medical and health discourse and communicated to the public. Sociological studies have demonstrated how colour‐blindness of medical discourse can obfuscate racism (Netherland & Hansen, 2017; Pryma, 2017; Whetstone, 2021). In particular, research that investigates eating and food‐related conditions often focus on the reproduction of race and class inequalities through diagnosis and treatment, finding that marginalised populations with the fewest choices are disproportionately impacted (Daniel, 2016; Papas et al., 2016; Walker et al., 2010) and blamed for their health outcomes (Firth, 2012; Saguy & Gruys, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Clive, a 58‐year‐old working‐class patient and one of the few Black men in the program, was routinely criminalized by staff and peers who made stigmatizing jokes about his “crackhead mentality,” asked him to tell “gang stories” (he was not in a gang) and set him up as a cautionary tale of the depths of unchecked addiction. Despite the real moments of catharsis that some reported, the rapid flip back into moralistic shaming for the program's token patients of color demonstrates how the humanizing tone of MRR was ultimately predicated on fictions of white innocence (Whetstone 2021).…”
Section: The Medicalization Of White Addictionsmentioning
confidence: 99%
“…While robust literatures suggest how race might shape “addict habitus” and treatment options, rehab is also a “racialized organization,” itself reproducing raced masculinities through intimate acts of self‐making (Whetstone 2021). Whiteness and white supremacy are embodied, actively performed, and reproduced through structures of the self (Du Bois 1995; Hooks 1997; Lipsitz 2006; Roediger 1998) and “white racial frames” encompassing images, stereotypes, emotions, and interpretations (Feagin 2020).…”
Section: Introduction and Literaturementioning
confidence: 99%